Ritmo e dinâmica: : A interseção sobre vivências de uma bailarina clássica oboísta - SILVA, Andréia Caroline Assunção da (2023)
This final paper was developed from my discomfort generated in Classical Ballet classes with the musical scores of my fifth-grade teacher at Escola de Dança Arte em Movimentos, a discomfort that I was able to study when I was approved in Musicalization and instrumentalization at the Instituto Estadual Conservatório de Música Carlos Gomes. And for this duality, sometimes Dance, sometimes Music, I suggested organizing this research by the Venn Diagram, named here as the “Arts Diagram”, with the general objective of analyzing the intersection components (rhythm and dynamics), to show that these converge with the Dance and Music sets. For this process, my experiences in Classical Ballet classes and Music classes were recorded. As the main guides of this research, the following authors dialogued: Débora Pinheiro, in her aspects of the “MUSIDAN” Symphony, which walks in both Dance and Music languages; Agrippina Vaganova, in her foundation of Classical Dance, master regent in my studies in Classical Ballet; Le Breton, with the study of the body in its social insertion. And for the musical language, the following authors dialogued: Bohumil Med, with the basic concepts of Music theory and Roy Benett, with the historical organization of Music. The research proved to be revealing regarding the enriching aspects of this body in constant research.